Valoração de patentes em universidades públicas do estado de São Paulo - Guimarães, Yuri Basile Tukoff (2013)
The enactment of the Brazilian Innovation Act in 2004 meant a stimulus to technological innovation and technology transfer from universities to the productive sector. In this context, the valuation of intangible assets consists in a fundamental activity in the transfer and licensing of technology to assign value to technologies protected under Industrial Property Rights of Scientific and Technological Institutions. However, the valuation of intangible assets is an incipient process when it comes to the context of Brazilian s universities Technology Transfer Offices (TTO). Thus, the objective of this work is to identify how the TTOs use the methods of valuation of patents in the process of assigning value to the technologies of public universities in the state of São Paulo. Additionally, it seeks to: identify how the valuation of patents is structured flowchart of activities in the TTO, analyze the importance of valuation within the activities of the NIT, with emphasis on its importance to the process of technology transfer from universities to businesses; identify the valuation methods used by universities analyzed in this study; ascertain how the NIT universities identifies the need to appraise its patents; identify which factors support and difficulty in valuing patents of public universities in the State of São Paulo; As research methodology will be conducted an exploratory and qualitative research strategy with multiple cases in four public universities TTOs in the state of São Paulo: UFSCar, Unesp, USP and Unicamp. It was found that the TTOs uses cost and market-based approaches, predominantly with the application of royalty rates and sunk cost methods, exclusively to support the negotiation of Industrial Property Rights for licensing to the productive sector. It is suggested for future work, the expansion of the scope of this paper to analyze the valuation in private universities, particularly in terms of its importance in the amounts to be received by the commercial exploitation of technologies transferred and / or patents licensed to the productive sector.